Una "Novela ejemplar" al teatro: hacia un estudio de las adaptaciones teatrales inglesas de Cervantes. - Argelli, Annalisa (Estudios Ingleses de la Universidad Complutense, 2001)
El casamiento engañoso, the eleventh novel of Cervantes’s Novelas ejemplares, has been transposed into the substance of the minor plot of John Fletcher’s popular comedy of manners Rule a Wife and Have a Wife. This study, after outlining the influence of the Spanish author on Jacobean English drama through overseas translations, traces the structure of Fletcher’s play as it is built from its Spanish source, presenting a thorough comparison of characters, denouement and language. 1.